2010
DOI: 10.1002/bit.22818
|View full text |Cite
|
Sign up to set email alerts
|

Construction of cellobiose phosphorylase variants with broadened acceptor specificity towards anomerically substituted glucosides

Abstract: The general application of glycoside phosphorylases such as cellobiose phosphorylase (CP) for glycoside synthesis is hindered by their relatively narrow substrate specificity. We have previously reported on the creation of Cellulomonas uda CP enzyme variants with either modified donor or acceptor specificity. Remarkably, in this study it was found that the donor mutant also displays broadened acceptor specificity towards several beta-glucosides. Triple mutants containing donor (T508I/N667A) as well as acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…which is particularly valuable for glycoside synthesis [147]. To further expand the acceptor specificity, De Groeve et al [149] identified a residue (E649) in the structure of CP from C. uda, whose side chain has hydrogen bonding with the D-Glc acceptor. Upon saturation mutagenesis of this residue, the mutant E649C was identified as being able to recognize new glucoside acceptors.…”
Section: Production Of Oligosaccharidesmentioning
confidence: 99%
“…which is particularly valuable for glycoside synthesis [147]. To further expand the acceptor specificity, De Groeve et al [149] identified a residue (E649) in the structure of CP from C. uda, whose side chain has hydrogen bonding with the D-Glc acceptor. Upon saturation mutagenesis of this residue, the mutant E649C was identified as being able to recognize new glucoside acceptors.…”
Section: Production Of Oligosaccharidesmentioning
confidence: 99%
“…A robust high-throughput screening platform is a prerequisite for targeted development of glycoside phosphorylases with altered substrate specificities to be employed in the synthesis of new glycosides. A triple mutant, containing both donor (T508I/N667A) and acceptor (E649C) mutations, was used as the starting point for creation of more promiscuous enzymes using semi-rational design and site-saturation mutagenesis.Two residues near the entrance of the active site, Asn-156 and Asn-163 were identified to define specificity towards anomerically substituted acceptors.While the wildtype can not glycosylate these acceptors at all, N156D/N163D/T508I/E649C/N667A showed activity towards alkyl-and aryl-β-glucosides and βlinked disaccharides, including β-cellobiosides whose glycosylated derivatives are of interest as novel surfactants, cellulose inhibitors or prebiotic sugars [94].…”
Section: Cellobiose Phosphorylasementioning
confidence: 99%
“…where G n denotes a β-glucan oligomer of length n (n ≥ 2), and G n + 1 denotes a β-glucan oligomer of length n + 1. Although CBP and CDP belong to the same glycoside hydrolase family, they have different substrate specificities 13, 14 .…”
Section: Introductionmentioning
confidence: 99%